Examination of language, cognitive, and mathematical skills in childhood endocrine diseases - Çavuşoğlu, Ebrar; Savaş, Merve; Dilek, Emine; Elgörmüş, Yusuf; Kahraman Beğen, Senanur (Frontiers in Psychology, 2024)
Introduction Children diagnosed with endocrine disorders may exhibit atypical development and may encounter challenges in language, academic, and cognitive skills, as well as social–emotional issues. The objective of this study was to identify potential therapeutic requirements in the areas of language, cognition, and mathematical skills among children with endocrine disorders who experience school failure. This will enable an early evaluation of speech and language disorders and the planning of interventions to be possible. Methods In this study, children with endocrine disorders were compared with their normally developing peers in terms of language, cognition, mathematical skills, and psychosocial characteristics. In this study, 15 children diagnosed with endocrine disorders (8 females, 7 males; mean age: 10, SD: 2) and 15 children with normal development (8 females, 7 males; mean age: 10, SD: 2) participated. The participants were subjected to the Test of Language Development-Primary: Fourth Edition Turkish Revision (TOLDP-4:T), the Turkish Nonword Repetition Test (TNRT), the Turkish Multilingual Sentence Repetition Test (LITMUS-TR), the Wechsler Intelligence Scale for Children (WISC-R), the Problem-Solving Test (PST), the Revised Child Anxiety and Depression Scale-Child Version (RCADS-CV), the Coopersmith Self-Esteem Inventory (CSEI), and the Child Behavior Checklist (CBCL). Results The findings of the study indicate that children with endocrine disease have lower performance in language, cognition, and mathematical skills compared to their healthy peers. Otherwise, they do not differ in terms of social–emotional status assessed by psychological scales. Discussion These findings suggest that while children with endocrine disorders face challenges in academic and cognitive domains, their social-emotional development remains relatively unaffected. Early identification and intervention in language, cognition, and mathematical skills may help address the academic struggles of these children, potentially improving their school performance and overall well-being.